Strategi, Alat dan Platform Keuangan Digital: Dampaknya pada Motivasi Kerja Karyawan dalam Tinjauan Literatur - Marjohan, Masno; Supratikta, Hadi; Hifny, Muhammad; Turnip, Jhon Sutrisno; Nur'aini, Eni; Yansyah, Rusli; Nurayani, Alinda (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the era of digital transformation, the integration of digital financial tools and platforms into organizational systems has reshaped how employees engage with their work. This study investigates the impact of digital financial technologies on employee motivation, highlighting both the opportunities and challenges that arise from this technological shift. The main issue addressed is the dual effect of such tools: while they can enhance financial literacy, efficiency, and employee satisfaction, they may also contribute to digital stress and privacy concerns. The purpose of this study is to examine how digital financial platforms influence work motivation by synthesizing findings from existing scholarly literature. Using a systematic literature review method, this research analyzes 38 journal articles, industry reports, and case studies published between 2019 and 2023, selected from academic databases such as ScienceDirect, SINTA, and Google Scholar. Thematic analysis was employed to identify key patterns related to employee motivation, financial well-being, technological adaptation, and organizational strategies. The findings show that digital financial tools positively impact employee motivation by increasing transparency, autonomy, and financial control. However, concerns related to cybersecurity, unfamiliarity with digital tools, and resistance to change may lead to anxiety and reduced motivation. The study concludes that companies must implement supportive strategies such as digital training, inclusive technology policies, and robust data protection measures to maximize the benefits of financial digitalization while minimizing its drawbacks.